Socio-Religious Education to Strengthen Harmony Between Hindus and Muslims with Multiculturalism - I Wayan Suwendra (Mimbar Ilmu, 2023)
The implementation of multicultural actions carried out by the community represents a life context that affirms differences. Different socio-cultural backgrounds do not make the local people segment but merge themselves into a diverse frame with the principle of egalitarianism. This study aims to analyze socio-religious education in the community to form collective awareness or a multicultural action in creating social relations. This research is classified as research using a qualitative approach. The subjects in this study were community leaders who played an important role in the village development process. Data collection in the study was carried out using observation, interviews, and document studies, with research instruments in the form of observation sheets and interviews. Data analysis techniques from this study include data collection, reduction, presentation, and conclusion. The study results show that social-religious education in Pegayaman Village has been well implemented. It can be seen from the synchronization and enculturation of Hindu conceptions of Tri Hita Karana and the conceptions of Islam, Faith, and Ihsan of Islam in various processes of community life. These two conceptions create a meeting point as a basis for universal religious values ​​that embody social actions that lead to the application of respect and acceptance of differences.